Trends and Efficacy of Interferon-Free Anti–hepatitis C Virus Therapy in the Region of High Prevalence of Elderly Patients, Cirrhosis, and Hepatocellular Carcinoma: A Real-World, Nationwide, Multicenter Study of 10 688 Patients in Japan. (15th April 2019) - Toyoda, Hidenori; Atsukawa, Masanori; Uojima, Haruki; Nozaki, Akito; Tamai, Hideyuki; Takaguchi, Koichi; Fujioka, Shinichi; Nakamuta, Makoto; Tada, Toshifumi; Yasuda, Satoshi; Chuma, Makoto; Senoh, Tomonori; et al.
Abstract: Background: We investigated changes in patient characteristics, rate of sustained virologic response (SVR), and factors associated with SVR after anti-hepatitis C virus (HCV) therapy with direct-acting antiviral (DAA) regimens in real-world practice in Japan, where patients with HCV are characterized by older age and high prevalence of cirrhosis and hepatocellular carcinoma (HCC). Methods: Changes in patient characteristics and SVR rates were evaluated from medical records among 10 688 patients who started interferon (IFN)-free DAA therapy between September 2014 and June 2018 in a nationwide, multicenter study. Factors associated with failure of SVR were analyzed. In particular, effects of cirrhosis or history of HCC on SVR were assessed by exact matching. Results: Patient age was becoming younger and baseline liver fibrosis was becoming milder over time. Overall SVR rate was 95.4%. The SVR rates increased over time in patients without a history of IFN-free DAA therapy. Multivariate analysis revealed that cirrhosis was unfavorably associated with achievement of SVR in both patients with genotype 1 (odds ratio, 1.68; 95% confidence interval [CI], 1.27–2.21) and genotype 2 (odds ratio, 1.69; 95% CI, 1.01–2.78). Comparisons after exact matching showed that the SVR rate was significantly lower in patients with cirrhosis than without it, whereas patients with and without a history of HCC had similar SVR rates. Conclusions: Background characteristics of patients who undergo IFN-free DAA therapy are changing in Japan. Patients without a history of IFN-free DAA therapy have high SVR rates. Exact matching confirmed that cirrhosis significantly influences the achievement of SVR in real-world settings.